Learning Loss in Chemistry: Basis for Conceptualizing a Remedial Program - Cascolan, Honelly Mae Segui (Department of Science Education, Universitas Sultan Ageng Tirtayasa, 2024)
The abrupt lockdown due to COVID-19 pandemic challenges the education institutions. School closure challenges the education institutions to develop strategies to continue instruction. Classes was moved online preventing students and teachers from meeting face-to-face. This study was conducted to determine the learning loss in Chemistry and to conceptualize a remedial program based on the identified learning loss. One hundred Bachelor of Secondary students major in Science academic year 2022-2023 was the respondents of the study. Researcher-made survey instrument was administered to the students through google form. Result showed that the learning loss of students is on the problem-solving skill and the analyzation of problems. There is also a learning loss on the basic concepts in Chemistry which is the foundation as you move to the higher Chemistry subject. It is recommended to have remedial program on the problem-solving skills of student, a laboratory experiment is also necessary for the students to visualized the volumetric and gravimetric analysis and to solve titration problems. A review of the basic concepts of Chemistry is also part of the remedial program in order that the students will have a strong background of chemistry concepts.